Engineering validamycin production by tandem deletion of γ-butyrolactone receptor genes in Streptomyces hygroscopicus 5008 - Gao‐Yi Tan; Yao Peng; Chenyang Lu; Linquan Bai; Jian‐Jiang Zhong (2014)
Paired homologs of γ-butyrolactone (GBL) biosynthesis gene afsA and GBL receptor gene arpA are located at different positions in genome of Streptomyces hygroscopicus 5008. Inactivation of afsA homologs dramatically decreased biosynthesis of validamycin, an important anti-fungal antibiotic and a critical substrate for antidiabetic drug synthesis, and the deletion of arpA homologs increased validamycin production by 26% (ΔshbR1) and 20% (ΔshbR3). By double deletion, the ΔshbR1/R3 mutant showed higher transcriptional levels of adpA-H (the S. hygroscopicus ortholog of the global regulatory gene adpA) and validamycin biosynthetic genes, and validamycin production increased by 55%. Furthermore, by engineering a high-producing industrial strain via tandem deletion of GBL receptor genes, validamycin production and productivity were enhanced from 19 to 24 g/L (by 26%) and from 6.7 to 9.7 g/L(-1) d(-1) (by 45%), respectively, which was the highest ever reported. The strategy demonstrated here may be useful to engineering other Streptomyces spp. with multiple pairs of afsA-arpA homologs.